EVALUASI PENERAPAN KINERJA BANGUNAN GEDUNG HIJAU MELALUI AUDIT KONSTRUKSI PADA PROYEK PERUMAHAN NASIONAL DI PURWAKARTA - Andani, Elsa Maryam; Windari, Aulia Choiri (Fakultas Teknik, Universitas Wiraraja, 2025)
The rapid growth of national housing development in Indonesia needs to consider sustainability aspects to reduce environmental impacts. One of the approaches applied is the Green Building concept, which focuses on energy efficiency, resource conservation, and good environmental quality. This study aims to evaluate the performance of Green Building implementation in a national housing project in Purwakarta Regency and to provide strategic recommendations for its improvement. This research uses a descriptive qualitative method with a case study approach, through document analysis and direct observation during the construction audit carried out by the Professional Expert Team of the Purwakarta Local Government, the Public Works and Housing Office ( Dinas PUPR), and assessors from Perum Perumnas. The assessment is based on the parameters stated in the Regulation of the Minister of Public Works and Housing No. 21 of 2021 (PERMEN PUPR No. 21/2021)concerning Green Building Performance Assessment. The results show that the project obtained a Green Building Certificate with an “Utama” (Excellent) rating of 80%, with the highest score in energy efficiency (40/46 points), followed by water efficiency (26/30 points), indoor air quality (16/18 points), and environmentally friendly materials (15/15 points). Meanwhile, site management (15/21 points), waste management (12/23 points), and wastewater management (8/12 points) were not fully optimized due to the limited application of rainwater conservation and integrated waste treatment systems. This study highlights the application of BGH in national housing projects through an official construction audit, which is still rarely explored, thus contributing to a better understanding of green building implementation in Indonesia.